ANALISIS FAKTOR YANG MEMENGARUHI PETANI MEMILIH POLA TANAM UBI KAYU SERTA EFISIENSI TEKNIS DI KABUPATEN LAMPUNG TENGAH - Manihuruk, Eka Monika; Harianto, Harianto; Kusnadi, Nunung (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2018)
The low production of cassava forcesIndonesia to import from other countries. The efforts to increase production and productivity are necessary in order to fulfill domestic needs. Cassava cultivation technology is expected to assist in increasing production. This study aims to analyze the factors that affect cassava farmers to choose cropping patterns and estimate technical efficiency in Lampung. Analytical methods used are binary logitto in 91 respondents with simple random sampling determine the factors that influence planting pattern and Data Envelopment analysis (DEA) to measure farmer efficiency level. Primary data used through questionnaire interview, and secondary data obtained from institution. The results showed that there are 4 significant variables that affect farmers' cropping pattern that is the area of land, the distance of land to the factory, the income while the education level hasno significant effect. Intercroppingfarmers are more efficiently than monoculture farmers with percentages of 77.41 and 45.